Tingkat Kepuasan Masyarakat Kecamatan Sumbawa Penerima Layanan Publik Oleh Kepolisian Resor Sumbawa - Mutiara Shofwah Dewi Nazhiroh; Aswar Tahir (INDO PUBLISHING, 2026)
Public service is a core function of the Indonesian National Police, requiring professional, transparent, and accountable delivery oriented toward citizen satisfaction. This study aims to measure public satisfaction levels among residents of Sumbawa District receiving services from the Sumbawa Resort Police. A quantitative descriptive approach was employed, with a population consisting of service users over the past three years. A sample of 100 respondents was determined using the Slovin formula, with stratified proportional and purposive sampling techniques. Data were collected through offline and online questionnaires, and the instrument was tested for validity and reliability. Descriptive statistics including frequency distribution, percentages, mean, median, mode, and standard deviation were used for analysis. The SERVQUAL model was applied, encompassing five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Findings indicate that overall public satisfaction falls within the satisfied category, with a mean score of 63.78 (SD = 7.16). The tangibles dimension achieved the highest average (3.00), while empathy recorded the lowest (2.63), though still within the satisfied range. This suggests that facilities and staff appearance are well-regarded, whereas personalized attention and understanding of community needs require further enhancement.In conclusion, services provided by the Sumbawa Resort Police have generally met public expectations. These results are expected to serve as evaluative input for maintaining service quality and improving areas that remain suboptimal, thereby fostering more effective and responsive public service delivery.